Pengaruh Motivasi, Pengetahuan Investasi, dan Internet of Things terhadap Keputusan Investasi Pasar Modal pada Masyarakat di Kabupaten Jember - Safa Natasha Aurellya; Hafidzi, Achmad Hasan; Nursaidah Nursaidah (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of information technology and the growing public awareness of the importance of financial planning have driven increased participation in capital market investments, particularly among the people of Jember Regency. However, low financial literacy and unequal utilization of technology remain challenges in making wise and sustainable investment decisions. This study aims to analyze the influence of motivation, investment knowledge, and the Internet of Things (IoT) on capital market investment decisions among the community in Jember Regency. The research method used is quantitative, employing a survey approach and multiple linear regression analysis. A total of 227 respondents, all members of a beginner investor community, were selected using purposive sampling with specific criteria. The results of the study indicate that all three independent variables motivation, investment knowledge, and the Internet of Things have a positive and significant influence on investment decisions. Investment knowledge was found to have the most dominant effect, followed by IoT and motivation. These findings highlight the importance of improving financial literacy and digital technology adoption in shaping rational investment behavior among local communities.